COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Rushana Inoyatova (Central Asian Journal of Theoretical and Applied Science, 2022)
This article is an attempt to formulate comprehensive ideas for EFL teachers based on the results of the studies by Sandra J. Savignon, a professor in the Program in Linguistics and Applied Language Studies at the Pennsylvania State University. The professor is popular with ELT teachers worldwide with her groundbreaking researches in the field of Second Language Acquisition. The paper provides an overview of the reasons why EFL teachers need to question their use of old simple memory-based methods and consider about the learners’ communicative competences in a deeper and meaningful manner. Own practical experience with developing communicative competence in Uzbek students in addition to a theoretical base is revealed in this work.